Black New Jersey : 1664 to the Present Day - Hodges, Graham Russell Gao (Rutgers University Press, 2018)
Black New Jersey tells the rich and complex story of the African American community's remarkable accomplishments and the colossal obstacles they faced along the way. Drawing from rare archives, historian Graham Russell Gao Hodges brings to life the courageous black men and women who fought for their freedom and eventually built a sturdy and substantial middle class. He explores how the state's unique mix of religious, artistic, and cultural traditions have helped to produce such world-renowned figures as Paul Robeson, Cory Booker, and Queen Latifah, as well as a host of lesser-known but equally influential New Jersey natives.